Home Works - A Cooking Book : Recipes for Organising with Art and Domestic Work - Richards, Jenny; Strandberg, Jens (Eindhoven : Onomatopee, 2020)
Ahlstrand, Anna ; Ariadad, Samira ; Bolaget ; Bornemark, Joanna ; Chang, Johnny ; Dillemuth, Stephan ; Ehrenbage, Marie ; Fanni, Maryam ; Federici, Silvia ; Hakonardottir, Audur Hildur ; Heberling, Rikard ; Hilal, Sandi ; Khadejeh-Nassiri, Lousie ; Lombard, Joanna ; Lundhal, Gunilla ; De Maximo, Dady ; Odumosu, Temi ; Othman, Khasrow Hamid ; Phillips, Ciara ; Richards, Jenny ; Strandberg, Jens ; Schultz, Kristina ; Óskardóttir, Halla Þórlaug ; Toncikeln ; Wuerth, Nathalie
Home Works – A Cooking Book: Recipes for Organising with Art and Domestic Work, expands on cooking with art and food as a process for coming together and building collectivity. The book highlights the art and politics of eating together through a number of artistic, curatorial and tasty dinner recipes. Recipes that nourish and nurture conversations around domestic labour, collaborative practices and feminist politics, expanded upon through a series of essays and interviews. The recipes were learnt during the cooking of Home Works; a research and exhibition programme investigating domestic labour and the politics of the home, hosted by the art space Konsthall C in Stockholm 2015-2017. Home Works – A Cooking Book is a tool for everyone that wants to use art to challenge what work we value and how work is organised. (provided by publisher)
boek